2012
DOI: 10.1016/j.euroneuro.2011.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The effects of oxytocin and its analog, carbetocin, on genetic deficits in sensorimotor gating

Abstract: Converging evidence from preclinical and clinical studies suggest that oxytocin has therapeutic potential for schizophrenia and other neuropsychiatric disorders. Prepulse inhibition of the startle reflex (PPI) is a measure of sensorimotor gating, an important brain function involved in filtering environmental information. We previously demonstrated that systemically administered oxytocin reversed psychostimulant-induced PPI deficits in rats suggesting that oxytocin can produce antipsychotic-like central effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
4
25
1
2
Order By: Relevance
“…For example, peripherally administered OT alters various aspects of social behavior and fear in rodents [4,5]. Similarly, our laboratory has demonstrated that subcutaneously (SC) administered OT enhances prepulse inhibition of the startle reflex (PPI), a centrally mediated index of sensorimotor gating an important feature of normal information processing [6,7], consistent with OT activity in the brain.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…For example, peripherally administered OT alters various aspects of social behavior and fear in rodents [4,5]. Similarly, our laboratory has demonstrated that subcutaneously (SC) administered OT enhances prepulse inhibition of the startle reflex (PPI), a centrally mediated index of sensorimotor gating an important feature of normal information processing [6,7], consistent with OT activity in the brain.…”
Section: Introductionmentioning
confidence: 82%
“…Peripherally administered OT enhances PPI deficits induced by psychotomimetic drugs and PPI deficits naturally exhibited in the Brown Norway (BN) rat strain [6,7]. The facilitation of reduced PPI is consistent with the effects of antipsychotic drugs (APDs) and suggests that OT may have therapeutic potential for schizophrenia.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Подобно окситоцину, пабал (карбето-цин) избирательно связывается с рецепторами окситоци-на в гладкой мускулатуре матки, стимулирует ритмичные сокращения матки, увеличивает частоту схваток и повы-шает тонус маточной мускулатуры [36]. В послеродовой матке пабал (карбетоцин) увеличивает скорость и силу спонтанных маточных сокращений.…”
Section: ключевые слова: послеродовые кровотечения профилактика лечunclassified
“…Эффективность различных доз пабала при внутри-венном и внутримышечном использовании оценивали по Российский вестник акушеРа-гинеколога 4,2016 данным записей токографии в течение 24-48 ч после срочных вагинальных родов у 40 женщин [36]. После од-нократного внутривенного болюсного введения 8-30 мкг или внутримышечного -10-70 мкг карбетоцина (пабал) отмечали тетаническое сокращение матки в течение 2 мин.…”
Section: ключевые слова: послеродовые кровотечения профилактика лечunclassified